2005
DOI: 10.1359/jbmr.2005.20.1.141
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With Once-Weekly Alendronate 70 mg Compared With Once-Weekly Risedronate 35 mg in Women With Postmenopausal Osteoporosis: A Randomized Double-Blind Study

Abstract: Once-weekly alendronate 70 mg and once-weekly risedronate 35 mg are indicated for the treatment of postmenopausal osteoporosis. These two agents were compared in a 12-month head-to-head trial. Greater gains in BMD and greater reductions in markers of bone turnover were seen with alendronate compared with risedronate with similar tolerability. Introduction:The nitrogen-containing bisphosphonates, alendronate and risedronate, are available in onceweekly (OW) formulations for the treatment of postmenopausal osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
72
6
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 38 publications
9
72
6
2
Order By: Relevance
“…Selection of the noninferiority margin was based on clinical relevancy of antifracture benefit. Previous studies of antiresorptive therapies (28)(29)(30)(31) demonstrated that lumbar spine BMD increases of 3% or more are associated with an antifracture benefit. In addition, the À2.0% noninferiority margin ensured that the combination therapy would be statistically superior to a putative placebo based on the data from the pivotal placebo-controlled teriparatide study by Neer and colleagues (3) using the method described by Hasselblad and Kong.…”
Section: Discussionmentioning
confidence: 99%
“…Selection of the noninferiority margin was based on clinical relevancy of antifracture benefit. Previous studies of antiresorptive therapies (28)(29)(30)(31) demonstrated that lumbar spine BMD increases of 3% or more are associated with an antifracture benefit. In addition, the À2.0% noninferiority margin ensured that the combination therapy would be statistically superior to a putative placebo based on the data from the pivotal placebo-controlled teriparatide study by Neer and colleagues (3) using the method described by Hasselblad and Kong.…”
Section: Discussionmentioning
confidence: 99%
“…There is comparative evidence that alendronate results in a greater reduction in bone turnover markers (BTMs) than risedronate [12] and that ibandronate results in an earlier response, but a reduction of similar magnitude to alendronate [13] .…”
Section: Introductionmentioning
confidence: 99%
“…(5)(6)(7) This was confirmed in a head-to-head study in which ALN produced significantly greater decreases in all biochemical markers of bone turnover compared to RIS in women with postmenopausal osteoporosis. (8,9) We have previously reported that RIS arrested the tissue aging encountered in untreated osteoporosis, (13) although it should be kept in mind that the study in that report was a clinical trial, thus potentially not representative of the ''real'' world due to likely compliance differences. (30)(31)(32)(33) In addition, differences have been seen in effects on intrinsic bone material properties in animal studies.…”
Section: Discussionmentioning
confidence: 98%
“…Unfortunately, the study was not powered to include fracture incidence as an outcome. (8,9) Bone quality (encompassing the structural and material properties of bone) is an important contributor to bone strength, (10) and depends on bone turnover as well as factors independent of bone turnover. (11) Spectroscopic analysis of biopsies from postmenopausal women who received either placebo or ALN (10 mg/d) for 3 years revealed no significant changes between the two groups in spectroscopic markers of bone quality (mineral/matrix ratio, crystallinity, carbonate/amide I ratio, and collagen maturity), except for a significant increase in cortical bone mineral content in the patients who were receiving ALN.…”
Section: Introductionmentioning
confidence: 99%